The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.6002/ect.2014.0253
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Costimulatory molecules are important factors determining the outcome of transplant. The aim of the present study was to investigate the effect of CTLA-4, CD28, PD-1, and ICOS gene polymorphisms on the outcome of kidney transplant. Materials and Methods: A total of 172 kidney transplant recipients were included in this study. There were 45 recipients (26%) who experienced acute rejection. The CTLA-4, PD-1, ICOS, and CD28 gene polymorphisms were evaluated by polymerase chain reaction and restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…After removing of 50 duplicated records, the remaining 101 studies were evaluated by carefully reading of titles, abstracts and full texts. After exclusion of additional 87 not relevant papers, 14 studies describing a total of 15 cohorts were included in the systematic review of association between CTLA-4 rs231775 and risk of acute renal graft rejection 13 19 , 29 , 30 , 42 46 . The main characteristics of the identified studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removing of 50 duplicated records, the remaining 101 studies were evaluated by carefully reading of titles, abstracts and full texts. After exclusion of additional 87 not relevant papers, 14 studies describing a total of 15 cohorts were included in the systematic review of association between CTLA-4 rs231775 and risk of acute renal graft rejection 13 19 , 29 , 30 , 42 46 . The main characteristics of the identified studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…CTLA-4 rs231775 was found in Hardy–Weinberg equilibrium (HWE) in 9 studies 14 – 19 , 30 , 43 45 ; it significantly deviated from HWE in three studies 16 , 29 , 42 , while it was not computable in two studies 13 , 46 which reported genotype data as a combined group (AG/AA vs. GG). The distribution of CTLA-4 rs231775 genotypes for each included cohort and timing of AR assessment after kidney transplantation is shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations